The tolerance balancing optimization with multiple constraints on the form and function of the discrete functional surface - Chuanyuan Zhou; Xiaomei Guo; Xiaoxiao Wei (Scientific Reports)
Abstract The working performance of the discrete functional surface is affected by the surface form. Both the surface form and the geometric function should be considered in tolerance design. However, the tolerance of different parts has different influence on the geometric function and surface form. This fact makes the tolerance optimization method focusing only on the geometric function requirements unreasonable for the discrete functional surface. In this regard, the tolerance balancing optimization with multiple constraints on the form and function is proposed. The crucial tolerances that significantly affect the surface form and geometric function of the discrete functional surface are extracted, which reduces the number of tolerances to be optimized. The tolerance optimization model with the penalty function considering the multiple constraints on the form and function is established. The tolerance contribution is incorporated into the nonlinear inertial weight particle swarm algorithm. By balancing the influence of tolerance on geometric function and surface form, and the extent of the tolerance optimization, the part tolerances that meet the requirements of geometric function and surface form are solved and the tolerance balancing optimization is achieved.